Optimasi Produksi Fibrinolitik oleh Bacillus megaterium BM 9.1 menggunakan media Limbah Pertanian sebagai sumber karbon - Kiki Lestari; Achmad Toto Poernomo; Prawita A (Berkala Ilmiah Kimia Farmasi, 2020)
The study of effect agro recidues carbon sources on fibrinolytic enzyme production by Bacillus megaterium BM 9.1 was done by using fibrin plate method. Bacillus megaterium BM 9.1 grown on agro residues medium with solid state fermentation. The fibrinolytic enzymes activity is declared by fibrinolytic index. Fibrinolytics index is the comparisson between clear zones and wall diameters. From various carbon sources tested, Bacillus megaterium BM 9.1 which is grown in banana peel, pineaple skin, corn husk, rice bran and corn cob could produce fibrinolytic enzymes. Optimum fibrinolytic activities found in a nutrient agar  and banana peel medium at fibrinolytic index 4,95 ± 0,08 (p<0,05). The comparisson fibrinolytic index  between Bacillus megaterium BM 9.1 which grown in combination nutrient agar, banana peel and nutrien agar standart is 117,%. Banana peel concentration optimation was done at concentration of 0,5 %, 1 %, 2 % and 4 % and the fibrinolytic index was found respectively according to 4,26 ± 0,11 ; 4,32 ± 0,03 ; 4,61 ± 0,03; and 4,35 ± 0,05. The optimum fibrinolytic activity was found in banana peel on consentration 2 %.